Transport institutions in Nigeria's livestock trade: a case study of the Bodija cattle market, Ibadan (2009)
"Using a qualitative method, this paper analyses the institutions in Nigeria’s livestock trade which enable an understanding of the actors and the nature of their interactions in the transportation of cattle from centres of production to the final consumers, using the Bodija cattle market in lbadan as the case study. This paper is viewed within Alonso’s General Theory of Movement, and by extension, Ullman’s bases of spatial interaction. Fixed routes are followed in a north-south direction, with extraneous time consuming and quite often risky overland doverage of the earliest stages o f movement, through railway carriage, though not without hitches. There road transport has dominated the movement of cattle in Nigeria, often by the private sector, not without its attendant problems though. Information was collected from leaders in cattle marketing and transportation, noting especially the ethnicity and gender relations. The data collection involved group interview, direct observations and extraction of relevant information from published sources. The findings show that formal and informal actors are involved in cattle transportation business. The movement of cattle to Akinyele was from the northern states. The choice of the marker by cattle dealers largely depends on prices at various source markets, easy availability of transport, and varieties of cattle species in demand. The availability of mobile phones has facilitated the exchange of information. Transportation is largely arranged through Yan Kwammssion (commissioned agents), and transport costs vary in proportion to the distance travelled."